The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.47750/pnr.2022.13.s06.283
|View full text |Cite
|
Sign up to set email alerts
|

Measuring bcr1 gene expression in C. albicans biofilm and its relation with persister cell

Abstract: Biofilm. formation by. pathogens in patients. was considered. a health problem. that leads to the emergence. of "antibiotic-resistant" isolates."Candida albicans" is the most .common. and dangerous. fungal pathogen. could form. biofilm in. various. sites of human body. Here , weinvestigated. the role of "bcr1 gene" on biofilm formation. as well as its correlation. with "persister cells" by using. crystal violet. stainingassay. and also quantification. of bcr1 gene expression. using "RT-PCR" . The results confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
(15 reference statements)
0
0
0
Order By: Relevance
“…The adhesion consider the first step to form biofilms [33]. Another study observed that C. albicans made as a base layer for P. aeruginosa when they build their own biofilms [34]. In other words, the interaction that occurs between bacterial and fungal isolates may be either antagonistic or synergistic, depending on the compatibility between different isolates [35].…”
Section: Discussionmentioning
confidence: 99%
“…The adhesion consider the first step to form biofilms [33]. Another study observed that C. albicans made as a base layer for P. aeruginosa when they build their own biofilms [34]. In other words, the interaction that occurs between bacterial and fungal isolates may be either antagonistic or synergistic, depending on the compatibility between different isolates [35].…”
Section: Discussionmentioning
confidence: 99%